Analisis Semiotika Psikologi Komunikasi pada Film Ku Kira Kau Rumah - Disti Adila Sani; Mitha Suheni; Siti Aisyah; Dita Khairiza; Maulana Andinata Dalimunthe (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to analyze the psychological communication contained in the film Ku Kira Kau Rumah. This study uses John Fiske's semiotic analysis technique which refers to The Codes of Television where film is a text and is studied through three stages, the level of reality, representation, and ideology. In this case, the author takes the sample of the film